The ukemis and judo practitioner: meaning, importance, enjoyment and discomfort. - Sebastião Iberes Lopes Melo; Saray Giovana dos Santos (Universidade Federal de Santa Catarina, 2003)
The objective this study was to investigate the opinion of Judo athletes on the meaning, importance, enjoyment and discomfort (physical and psychological) of "ukemis", and also about the materials used for different types of practice. Eighty-six Judo athletes were interviewed at competitions during 2001 in the state of Santa Catarina, Brazil,. The mean age of subjects was 21.59 ± 6.49 years. The results demonstrated that the sample: is heterogeneous in terms of how long they practice Judo for and homogeneous in judo grade (belt color, etc.). The performance of these subjects was very good during the last two years. They didn't have a clear idea of the meaning and important of "ukemis" in Judo. The Judo athletes preferred synthetic tatamis to train "nage-waza" and competition and traditional tatamis to train "katame-waza". Discomfort when practicing "ukemis" was independent of the enjoyment and of number of "ukemis" executed during the training session, and preference for type of tatami was independent of practicing time. RESUMO O objetivo deste estudo foi investigar a opinião dos judocas sobre a prática dos "ukemis", com relação ao signifi cado, importância, gosto e desconforto (físico e psicológico), e, sobre os materiais (tatames) utilizados para tal. Entrevistou-se durante as competições catarinenses de 2001, 86 judocas, com média de idade de 21,59 ± 6,49 anos. Analisando as respostas concluiu-se que o grupo: é heterogêneo quanto ao tempo de prática, porém homogêneo quanto à graduação, e apresentou um bom desempenho nos últimos dois anos; grande parte dos judocas não têm bem defi nido o signifi cado e a importância do "ukemi" para a prática do judô; o número dos "ukemis" realizados por treino é independente da graduação dos judocas; os judocas preferem o tatame sintético para os treinamentos em pé e competições, e o de palha, para o treinamento no solo; o desconforto sentido pelo judoca na realização dos "ukemis" independe do tempo de prática; a dor percebida pelo judoca independe tanto do gostar de realizar quanto do número de "ukemis" realizados por treino; a preferência pelo tipo de material para a prática em diferentes situações, independe do tempo de prática (experiência) do judoca.